Response of Soil Bacterial Community Diversity and Composition to Time, Fertilization, and Plant Species in a Sub-Boreal Climate - Li, Honghong; Penttinen, Petri; Mikkonen, Anu; Stoddard, Frederick L.; Lindström, Kristina (Frontiers in Microbiology, 2020)
Pastures are an important part of crop and food systems in cold climates. Understanding how fertilization and plant species affect soil bacterial community diversity and composition is the key for understanding the role of soil bacteria in sustainable agriculture. To study the response of soil bacteria to different fertilization and cropping managements, a three-year (2013-2015) field study was established. In the split-plot design, fertilizer treatment (unfertilized control, organic fertilizer and synthetic fertilizer) was the main plot factor, and plant treatment (clear fallow, red clover (Trifolium pratense), timothy (Phleum pratense) and a mixture of red clover and timothy) was the sub-plot factor. Soil bacterial community diversity and composition, soil properties and crop growth were investigated through two growing seasons in 2014 and 2015 with different nitrogen input levels. The community diversity measures (richness, Shannon diversity and Shannon evenness) and composition changed over time (P < 0.05) and at different time scales. The community diversity was lower in 2014 than in 2015. The temporal differences were greater than the differences between treatments. The overall correlations of Shannon diversity to soil pH, NO3-, NH4+ and surplus nitrogen were positive and that of bacterial richness to crop dry matter yield was negative (P < 0.05). The major differences in diversity and community composition were found between fallow and planted treatments and between organic and synthetic fertilizer treatments. The differences between planted plots were restricted to individual OTUs. Soil moisture, total carbon content and total nitrogen content correlated consistently with the community composition (P < 0.05). Compared to the unfertilized control, the nitrogen fertilizer loading enhanced the temporal change of community composition in pure timothy and mixture more than that in red clover, which further emphasizes the complexity of interactions between fertilization and cropping treatments on soil bacteria.